2020
DOI: 10.1016/s2468-2667(20)30164-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 among front-line health-care workers and the general community: a prospective cohort study

Abstract: Summary Background Data for front-line health-care workers and risk of COVID-19 are limited. We sought to assess risk of COVID-19 among front-line health-care workers compared with the general community and the effect of personal protective equipment (PPE) on risk. Methods We did a prospective, observational cohort study in the UK and the USA of the general community, including front-line health-care workers, using self-reported data from the COVID Symptom … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

80
1,600
10
51

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,836 publications
(1,833 citation statements)
references
References 28 publications
80
1,600
10
51
Order By: Relevance
“…[13][14][15] Overall, our results corroborate presumptions regarding the correlation between various risk factors and HCW infection with more recent studies showing adequacy of PPE, clinical settings, gender and ethnic background as important factors of HCW infection. [22][23][24][25] Our sample of HCWs, overall had higher reported COVID-19 infection risk (29%) compared with general population estimates. 26 Furthermore, unlike other studies, we sampled a diverse set of HCWs and explored the impact of secondary factors, including specific role in the healthcare industry, the effects of isolation while being infected, the risks of family members, and the effects of coworkers being afflicted with COVID-19 on psychological wellbeing.…”
Section: Discussionmentioning
confidence: 60%
“…[13][14][15] Overall, our results corroborate presumptions regarding the correlation between various risk factors and HCW infection with more recent studies showing adequacy of PPE, clinical settings, gender and ethnic background as important factors of HCW infection. [22][23][24][25] Our sample of HCWs, overall had higher reported COVID-19 infection risk (29%) compared with general population estimates. 26 Furthermore, unlike other studies, we sampled a diverse set of HCWs and explored the impact of secondary factors, including specific role in the healthcare industry, the effects of isolation while being infected, the risks of family members, and the effects of coworkers being afflicted with COVID-19 on psychological wellbeing.…”
Section: Discussionmentioning
confidence: 60%
“…Health disparities permeate medical care and researchers have noted that many marginalized ethnic minorities are considered frontline essential workers and do not have the socioeconomic backing to shelter in place [20,21]. Researchers have revealed a threefold increased risk of positive COVID-19 testing among frontline healthcare workers in western countries [22]. The disproportionate occupational hazard among Blacks and Hispanics has been well documented [23], and the prevalence of workrelated disabilities is nearly twice as high among Blacks over 50 years old when compared with their White counterparts [24].…”
Section: Discussionmentioning
confidence: 99%
“…Personal protective equipment and sufficient resting time is the need of the hour [17]. Front-line health-care workers were at increased risk for reporting a positive COVID-19 test adequacy of PPE, clinical setting, and ethnic background are important factors that should be considered [18]. China's National Health Commission identified that more than 3300 health-care workers were infected until March while local media had already reported 22 deaths by the end of February.…”
Section: Discussionmentioning
confidence: 99%